Robot Boat Design For Real-Time Monitoring Of River Water Quality - Prabowohendhi, Santra; Yuamita, Ferida; Jati Nugroho, Andung (University of Technology Yogyakarta, 2020)
As the population grows in big cities and watersheds, it will significantly impact river waters. One of the settlements located on the banks of the river Winongo is Ngampil village, Ngampil sub-district, Yogyakarta City. According to data from the Yogyakarta City Central Statistics Agency, the population of the Ngampil sub-district increased in 2018 to 18,591 inhabitants, from 2016 with 10,540 inhabitants, the Winongo River is used by the Ngampil residents for fish farming by making cages and also residents who use the Winongo River for activities environmental conservation. One effort to control water pollution is to monitor water quality consistently. The problem in this research is the absence of tools to monitor river water quality. Therefore, it is necessary to design an efficient monitoring tool to read water quality with a ph indicator in real-time using the hovercraft method through the internet of things method. Utilizing this robot boat tool can monitor river water quality using an automatic drive system and display the river water's pH indicator on the website. This research showed river water quality at 6:00 in the morning with a pH value of water 6.81 information Poor / Contaminated by Weight, daytime at 12.00 with a pH value of water 6.77 information Poor / Contaminated by Weight, and afternoon at 18.00 with a water ph value of 6.66 information Poor / Severely polluted.